LncRNA H19 acts as a ceRNA to promote glioblastoma malignancy by sponging miR-19b-3p and upregulating SERPINE1 - Wonyi Jang; Mijung Im; Goeun Yoon; Jungwook Roh; Wanyeon Kim (Cancer Cell International)
Abstract Background Glioblastoma (GBM) is a highly aggressive brain tumor, characterized by genetic complexity and resistance to treatment. Despite significant advancements in cancer research, the mechanisms driving GBM progression remain poorly understood. This study investigates the molecular pathways associated with GBM, and focuses on long non-coding RNA H19 and its role in tumor growth and progression. Methods Analysis of Gene Expression Omnibus (GEO) dataset was performed to identify differentially expressed genes in GBM cells with H19 overexpression, revealing serpin family E member 1 (SERPINE1) as a potential target. Bioinformatics analyses were used to evaluate the differential expression of H19 and SERPINE1 in GBM tissues, perform survival analysis, and predict miR-19b-3p as a candidate miRNA. The expression levels of H19, miR-19b-3p, and SERPINE1 were validated using RT-qPCR and Western blotting. Dual-luciferase reporter assays were conducted to confirm the direct interactions between H19, miR-19b-3p, and SERPINE1. Cell viability and motility assays were performed to assess the effects of modulating H19/miR-19b-3p/SERPINE1 expression on cell survival, migration, and invasion. Results Bioinformatics analyses identified SERPINE1 as an oncogene upregulated in GBM cells with H19 overexpression, and the overexpression of H19 and SERPINE1 was linked to poor prognosis in GBM patients. Experimental validation demonstrated that H19 upregulates SERPINE1 expression, while miR-19b-3p directly binds to both H19 and SERPINE1, suppressing SERPINE1 expression. Functional assays further confirmed that H19 promotes cell survival, migration, and invasion, whereas miR-19b-3p inhibits these processes by downregulating SERPINE1. Conclusions These findings reveal a novel mechanism whereby H19 drives GBM progression by acting as a competing endogenous RNA (ceRNA) to sponge miR-19b-3p and upregulate SERPINE1 expression. Our results offer new insights into the regulatory interplay among H19, miR-19b-3p, and SERPINE1 in GBM cell lines, a relationship that has not been clearly defined in previous research. Moreover, the H19/miR-19b-3p/SERPINE1 axis highlights the potential use of H19, miR-19b-3p, and SERPINE1 as promising biomarkers and therapeutic targets in GBM.